Seed Polymer Coating with ZnO, SiO2 and TiO2 Nanoparticles: An Innovative Seed Quality Enhancement Technique in Sweet Pepper - LAXMI DUNDAPPA CHOUGALA; PARASHIVMURTHY; HARISH MS; R SIDDARAJU (Seed Research, 2024)
A laboratory study was undertaken to assess the effect of seed polymer coating with ZnO, SiO2 and TiO2 nanoparticles (NPs) at different concentrations (250 and 500 ppm) on different seeds of vigour lots in sweet pepper at Department of Seed Science and Technology, University of Agricultural Sciences, Bangalore. Among vigour level, high vigour seed lots differed significantly with highest seed germination (84.0%), speed of germination (9.54), mean seedling length (11.53 cm), mean seedling dry weight (4.07 mg), seedling vigour index – I (952), seedling vigour index – II (342), total dehydrogenase activity (1.654), total soluble seed protein (68.24 µg/g), amylase activity (85.47 µmol/min) and decreased electrical conductivity of seed leachates (35.91 µS/cm).Among treatments, seed polymer coating with ZnO NPs at 250 ppm recorded significantly higher seed germination (82.0%), speed of germination (9.22), mean seedling length (11.41 cm), mean seedling dry weight ( 4.24 mg), seedling vigour index – I (937)seedling vigour index - II (348), total dehydrogenase activity (1.506), protein content (72.80 µg/g) and á-amylase activity (76.30 µmol/min) and lowest electrical conductivity (30.64 µS/cm) over control, followed by SiO2 and TiO2 NPs at 250 ppm. However, higher concentrations of NPs reflected inhibitory effect on seed germination and seedling growth (nano ZnO, SiO2 and TiO2 at 500 ppm each).Based on the seed quality evaluation, it was concluded that seed coating with ZnO NPs at 250 ppm can be used to enhance of sweet pepper.